Characterization of Thyroid Nodules by 4-Dimensional Computed Tomography: Initial Experience. Issue 2 (March 2017) - Fitzgerald, Ryan T.; Kuruva, Manohar; David, Ryan; Samant, Rohan S.; Kumar, Manoj; Van Hemert, Rudy; Angtuaco, Edgardo J.; Bodenner, Donald; Stack, Brendan C.
Abstract : Objective: We aimed to evaluate the use of 4-dimensional computed tomography (4DCT) for characterization of thyroid nodules. Methods: Our study drew from 100 consecutive patients with primary hyperparathyroidism who underwent 4D parathyroid CT imaging for adenoma localization. Included subjects had tissue sampling of a thyroid nodule within 3 months of 4DCT. Results: Twenty subjects (18 women and 2 men) had thyroid nodules that were pathologically confirmed. Precontrast nodule attenuation was significantly lower in malignant nodules when compared with benign nodules (36 vs 61 HU, P = 0.05). Arterial phase and delayed phase nodule attenuations were not significantly different in malignant and benign nodules (128 vs 144 HU, P = 0.7; 74 vs 98 HU, P = 0.3). Conclusions: Our initial experience with a small group of patients was unable to support the use of 4DCT for characterizing thyroid nodules; however, precontrast nodule attenuation was significantly lower in malignant nodules when compared with benign nodules.